’n Bepaling van die behoefte aan voetversorging by ’n groep bejaardes - Y Bothma (Curationis, 1985)
A survey was done to determine the demand for foot care amongst groups of elderly people in old age homes. A history was taken and a clinical examination was done according to criteria on an evaluation scale to determine the extent of foot-problems amongst the sample. The results indicated that 93% of the elderly had foot-problems and that 46,51 % of these people tried to take care of their own feet.